2011
DOI: 10.1080/10413200.2010.543120
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Talent Development Environment on Achievement Goals and Life Aspirations in Singapore

Abstract: Producing successful athletes in Singapore is a high priority, and the financial rewards for those that make it are great. In light of such an extrinsically motivated structure, the purpose of the current study was to examine the impact of the talent development environment on the goal pursuits and life aspirations of young athletes. Intrinsic goal striving was predicted by a mastery approach and an environment that prioritized long-term development and fundamentals, and provided a good support network. On the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 28 publications
0
14
1
1
Order By: Relevance
“…Mills, Butt, and Maynard (2014) have used the TDEQ as a tool to review environments of UK football academies and they suggested the need to build a strong environment at the academies. A number of researchers have investigated the role of the environment on motivational characteristics of developing athletes (e.g., Wang et al, 2011;Wang, Pyun, Li, & Lee, 2016). Furthermore, work examining the role of the environment on the stress, wellbeing, and burnout of athletes has also been conducted (e.g., Ivarsson, Stenling, Fallby, Johnson, Borg, & Johansson, 2015;Li, Wang, & Pyun, 2017a).…”
Section: Talent Development Environmentmentioning
confidence: 99%
“…Mills, Butt, and Maynard (2014) have used the TDEQ as a tool to review environments of UK football academies and they suggested the need to build a strong environment at the academies. A number of researchers have investigated the role of the environment on motivational characteristics of developing athletes (e.g., Wang et al, 2011;Wang, Pyun, Li, & Lee, 2016). Furthermore, work examining the role of the environment on the stress, wellbeing, and burnout of athletes has also been conducted (e.g., Ivarsson, Stenling, Fallby, Johnson, Borg, & Johansson, 2015;Li, Wang, & Pyun, 2017a).…”
Section: Talent Development Environmentmentioning
confidence: 99%
“…High quality development environments have been shown to focus on the growth of intrinsic motivation and emphasis the selfdevelopment of youth athletes (Martindale et al, 2010). More specifically, talent development environments that emphasized fundamental skill progression in the context of long term development, within a robust support network, have been shown to positively influence intrinsic goal striving (Wang et al, 2011). This developmental and supportive approach may be of importance given that striving to achieve an intrinsic goal has been related to an enhanced well-being, greater confidence, greater learning capacity, and reduced stress in youth athletes (Vansteenkiste et al, 2004;Ivarsson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…En general, los varones se orientan más a lograr metas extrínsecas, es decir aquellas que no tanto tienen que ver con la superación y el esfuerzo, sino con el ser mejor que los demás y obtener recompensas por estos logros, como podrían ser la fama o la riqueza. A modo de ejemplo, se han encontrado relaciones entre las aspiraciones extrínsecas de deportistas adolescentes de élite con las metas de evitación del fracaso (tanto en cuanto a la maestría como en lo referente al rendimiento) (Koh y Wang, 2015;Wang et al, 2011). Por el lado de las mujeres, podría pensarse que a través del proceso de socialización, los adolescentes reciben la influencia del contexto en el que viven y van construyendo sus creencias y conductas con respecto a la importancia y el valor del deporte para ellos.…”
Section: Discussionunclassified